Screening, isolation and molecular characterization of a thermostable xylanases from indigenous thermophilic fungus, thermoascus aurantiacus - Ang, Chung Huap (Universiti Malaysia Sarawak (UNIMAS), 2007)
Twelve thermophilic and thermotolerant indigenous fungi were successfully isolated from soil and water samples of various locations in Malaysia using pour plate method. Of all the fungi isolated, ten of them were confirmed as thermophilic fungi with optimal growth temperature of 55°C. The other two were categorized as thermotolerant fungi with optimal growth temperature between 37°Cto 45°C. All isolates were screened for their ability to secrete thermostable xylanases by using the standard dinitrosalicylic acid (DNS) assay. A Thermoascus aurantiacus isolate (WW1) obtained from Gadek Hot Spring (Melaka) was selected as the best xylanase producing fungus. WW1 has secreted 127.87 U/mL and 105.20 U/mL of crude xylanase in minimal medium containing 1% (w/v) birch wood xylan and 1% (w/v) corn cobs after 14 days of incubation period at 55°C, respectively. The WW1 crude xylanase has an optimum activity at temperature between 55°C to 60°C and pH 5.0. The crude enzyme also stable over a board range of pH ranging from pH 4.0 to pH 12.0 and temperatures ranging from 50°C to 70°C. In addition, a maximum xylanase secretion was achieved by WWl after 12-days of incubation period at 55°C in 1% (w/v) birch wood xylan medium. Apart from secreting thermostable xylanase, WW1 also secreted 81. 75 U/mL of cellulase, indicating that the xylanase of WW1 belongs to family 10 xylanases. Purification of WW1 crude xylanase was successfully carried out through ultrafiltration, hydrophobic interaction chromatography (HIC) and ion exchange chromatography (lEX). The specific enzyme activity for the final purified xylanase was 2.1 folds higher compared to crude enzyme concentrated through ultrafiltration. From the sodium-dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis, the estimated molecular weight for WW1 purified xylanase was 35 kDa. Under optimal assay condition, the purified xylanase has a maximum enzyme activity in 50mM citrate buffer with pH 5.0. The highest enzymatic activity also detected at temperature between 55°C and 60°C. Purified WWl xylanase also stable at pH 6.0 to pH 9.0 as it has retain at least 60% of the initial xylanase activity even after one hour incubation in buffers with pH 6.0 to pH 9.0. Apart from that, the purified enzyme also exhibits a moderately high thermostability with temperatures ranging from 40°C to 70°C. An attempt has successfully carried out to isolate putative xylanase gene from WWl. Amplification of putative thermostable xylanase gene was conducted by using direct polymerase chain reactions (PCR) and reverse transcription polymerase chain reactions (RT-PCR) with several sets of sequence specific PCR primers. A PCR product with molecular size of approximately 2.5 kb was successfully obtained by using XynA3 (Forward) and XynA3 (Reverse). Additionally, a 500 bp RT-PCR product was also successfully obtained by using the XynAl (Forward) and XynAl (Reverse). After compared with all the available xylanase genes sequences in the National Center for Biotechnology Information (NCBI) GenBank, the nucleotide sequences for both PCR fragments were most similar to Thel'moascus aurantiacus endo-l, 4-beta-xylanase A (xynA) gene (Accession number:AJ132635 and Accession number: AF127529). It was observed that the 2.5 kb PCR fragment shows a high homology (92% similarity) towards Xyn A gene of T. aurantiacus. Meanwhile, the RT-PCR product was confirmed as partial sequence of T. aurantiacus thermostable xylanases mRNA with original molecular size of 900 bp. The amino acids sequence of the RT-PCR product also shows 47% and 49% similarity towards amino acids sequences of T. aurantiacus xylanase (Xyn A) and T. aurantiacus Xylanase I (Chain A) respectively.